ANALISIS PENGARUH DANA ALOKASI UMUM DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA SELATAN - Shella Andita Astria (Department of Development Economics, Universitas Sriwijaya, 2014)
This study aims to determine how the effect of the General Allocation Fund (DAU) and capital expenditure on economic growth. The data used in this study is secondary data, that is data from 2003 through 2010 This study used quantitative and qualitative analysis techniques, which use quantitative analysis Multiple regression through SPSS. Regression results show that the DAU negative effect on economic growth, while capital expenditures and significant positive effect on economic growth in South Sumatra province. From the regression results DAU and capital expenditure on economic growth seen R2 value of 0.606 indicates the independent variable is able to explain the dependent variable of 60.6 percent (significant). This means that 60.6 percent of variable economic growth in 2003-2010 was able to be explained by the variable general allocation fund (DAU) and capital expenditure, while the remaining 39.4 percent is influenced by factors outside the model are held constant. The result using the elasticity coefficient of elasticity of 21.2 percent for DAU and 23.9 percent for capital expenditure which means is elastic (e> 1). This shows that the general allocation fund and capital expenditures considerable influence respectively is 21.2 percent and 23.9 percent. Keywords: Economic Growth, the General Allocation Fund, Capital Expenditure, Multiple Linear Regression and Elasticity